The Influence of Locus of Control and Internship Experience on the Work Readiness of Vocational Education Students - Hidayatulloh, Muhammad Kris Yuan; Ekohariadi, Ekohariadi; Suparji, Suparji; Çobanoğlu, Ömer (Cita konsultindo, 2024)
This study aims to analyze: (1) the impact of locus of control on mechanical engineering students' willingness to work; (2) the impact of practical experience on the work willingness of mechanical engineering students; and (3) the simultaneous influence of locus of control and practical experience on the willingness to work of mechanical engineering students. This study uses ex post facto methods through a quantitative data approach using research question instruments distributed for vocational students. Data was obtained from 72 students as samples selected for analysis using regression. The results of this study found: (1) there is a positive effect between locus of control on students' willingness to work in mechanical engineering skills; (2) there is a positive effect between practical experience on students' willingness to work in mechanical engineering skills; and (3) there is a positive effect between locus of control and practical experience simultaneously on students' willingness to work in mechanical engineering competencies.